1996
DOI: 10.1210/jc.81.10.3553
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine content and in vitro catecholamine synthesis in peripheral human lymphocytes

Abstract: We studied the catecholamine (CA) content in peripheral human lymphocytes and the ability of these cells to synthesize CA in vitro. CA were separated by high performance liquid chromatography (HPLC) and determined in the supernatant by electrochemical detection as well as being determined after ultrasonic cell disruption in mononuclear leukocytes, adherent cells (monocytes/macrophages), total lymphocytes, and B- and T-cell enriched fractions. T lymphocytes contained L-Dopa and norepinephrine (NE), whereas B ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 0 publications
0
16
1
Order By: Relevance
“…In addition to their hormonal and neurotransmitter roles, catecholamines also influence immune responses, and the importance of this neural-immune cross-talk via neurotransmitters and cytokines has been increasingly recognized [2]. For instance, stimulation of the vagus nerve can regulate inflammatory cytokine production, and conversely, macrophages and lymphocytes are able to synthesize catecholamines that influence the central nervous system (CNS) [35]. Additionally, immune cells express adrenergic receptors and are therefore responsive to catecholamines [6].…”
Section: Catecholaminesmentioning
confidence: 99%
“…In addition to their hormonal and neurotransmitter roles, catecholamines also influence immune responses, and the importance of this neural-immune cross-talk via neurotransmitters and cytokines has been increasingly recognized [2]. For instance, stimulation of the vagus nerve can regulate inflammatory cytokine production, and conversely, macrophages and lymphocytes are able to synthesize catecholamines that influence the central nervous system (CNS) [35]. Additionally, immune cells express adrenergic receptors and are therefore responsive to catecholamines [6].…”
Section: Catecholaminesmentioning
confidence: 99%
“…The catecholamines (CAs), including dopamine (DA), epinephrine (E) and norepinephrine (NE), were considered mainly as conventional neurotransmitters and neuroendocrine mediators; however, there is now robust evidence that they are also produced by cells of the immune system [1,2,3,4,5,6,7,8]. Our previous studies also indicate that lymphocytes express tyrosine hydroxylase (TH), a rate-limiting enzyme of CA synthesis, and the three kinds of CAs exist in lymphocytes and inhibit concanavalin A (Con A)-induced lymphocyte proliferation and interleukin (IL)-2 production through autocrine/paracrine pathways [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Four years later [38], the same research group confirmed the presence of DA, L-DOPA, and norepinephrine in PBL by electrospray ionization mass spectroscopy. In 1996, Musso et al [39] studied catecholamine content in human PBL and the ability of these cells to synthesize catecholamines in vitro . Catecholamines were separated by high performance liquid chromatography (HPLC) and electrochemical detection.…”
Section: The Dopaminergic System In Peripheral Blood Lymphocytesmentioning
confidence: 99%